A Review on the Role of Probiotics and Prebiotics in Human Health - Harshkumar N Patel; Amar C Sajjan; Sanyuth Reddy Regalla; Anand Jadhao; Jitendra Patel (Disease and Health: Research Developments Vol. 7, 2025)
Probiotics and prebiotics play a crucial role in maintaining human health by modulating the gut microbiota, enhancing immune function, and preventing various diseases. Probiotics, which are live microorganisms, confer health benefits when administered in adequate amounts, while prebiotics, which are non-digestible dietary fibres, promote the growth of beneficial bacteria in the gut. Their synergistic action has been linked to improved gastrointestinal health, reduced inflammation, enhanced metabolic functions, and potential applications in oral and systemic diseases. Recent advancements in research highlight their role in modulating the gut-brain axis, reducing the risk of chronic diseases, and improving overall well-being. This review explores the mechanisms, clinical applications, and future prospects of probiotics and prebiotics in human health.